Bringing the Marginalized into Epistemology - Oduro, Kelly (Stance: an international undergraduate philosophy journal, 2022)
In this paper, I discuss the epistemological injustices that Black women face in academia. I review Patricia Hill Collins’s work, “Learning from the Outsider Within: Sociological Significance of Black Feminist Thought,” which details the unique knowledge standpoint that Black women possess. I build upon the ideas set forth by Collins and other scholars to understand how the traditional knowledge validation process is tainted with political implications and harms Black women. I then offer recommendations rooted in alternative epistemology principles to combat the injustices inherent in academia.